Prestasi Kerja Karyawan Meubel di Komplek Industri Kota Palangka Raya (Work Achievement of Furniture Employees in an Industrial Complex Palangka Raya City) - Surasana, I Nyoman; Dulamin, Jumri; Dolit (Jurnal Hutan Tropika, 2019)
The research objectives were to find out: skill levels, work achievement (in producing tables, cabinets, and doors), differences in work achievement, and wage rates received by employees in each type of product. The study used the Non Stop Method and analyzed the data with the t-Test. The results showed that the highest average work unit (unit /week) on door products (4.25), following wardrobe products (4.16) and the smallest on table products (4.06). The more skilled the employee, the greater the work achievement, and vice versa. Employee achievement II (medium skills) on desk and cupboard products> employee I (less skilled) at ? 5%, employee achievement III (skilled) on wardrobe products> employee I at ? 1%. In the product door, employee achievement II> employee I at ? 1%, and employee achievement III> employee I at ? 5%. Based on the level of wages received by employees (Rp. / week) the most unattractive product to beworked on (produced) is a table.